AD9850 based function generator - Yusuf Fernades, Rudi; Sapto Aji, Wahyu (Signal and Image Processing Letters, 2019)
Function generator consists of the main generator and a modulation generator. The main generator provides sine, square, or triangular wave output with a frequency range of 0.01Hz to 13MHz. The modulation generator generates sine, square, and triangle waveforms with a frequency range of 0.01Hz to 10kHz. The input signal generator can be used as Amplitude Modulation (AM) or Frequency Modulation (FM). The AM envelope can be adjusted from 0% to 100%, while the carrier frequency of FM can be set up to± 5%. Function generator generally produces frequencies in the range of 0.5Hz to 20MHz or more depending on the manufacturer's design. The resulting frequency can be selected by rotating the frequency range knob. The amplitude signal can be adjusted within a range from 0.1V to 20Vpp (peak-to-peak voltage) at no-load conditions and 0.1V to 10Vpp with a load of 50ohms. The main output is specified by SYNC Output. This research makes a wave generator and its frequency, as well as DDS AD9850 as a wave reader sensor on the oscilloscope using Arduino Uno to generate waves and a rotary encoder as a frequency regulator. Based on the experiment by varying frequency, peak-to-peak voltage and period are produced as follows: if the frequency at 50Hz, then the peak-to-peak voltage is 1.2Vpp and period (T) is 0.006s if the frequency at 100Hz, then the peak-to-peak voltage is 1.2Vpp and period is 0.005s if the frequency at 150Hz then the peak-to-peak voltage is 1.2Vpp and period is 0.034s if the frequency at 1KHz then the peak-to-peak voltage is 1.2Vpp and period is 0.0006s if the frequency at 1.5KHz then the peak-to-peak voltage is 1.2Vpp and period is 0.0004s, and finally if the frequency at 2KHz then 1.2Vpp and period are 0.000225s.